2010
DOI: 10.1007/s00432-010-0960-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and prognosis in a breast cancer cohort

Abstract: In this study, patients with diabetes and oestrogen receptor negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes. Diabetes was also associated with an almost 2-fold increase in mortality within the 5 years follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
3
56
1
Order By: Relevance
“…These results are consistent with a (17). However, in the study by Schrauder et al, the ER-negative patients with T2DM also exhibited a higher distant metastasis risk than those without T2DM.…”
supporting
confidence: 86%
“…These results are consistent with a (17). However, in the study by Schrauder et al, the ER-negative patients with T2DM also exhibited a higher distant metastasis risk than those without T2DM.…”
supporting
confidence: 86%
“…Breast cancer patients with type II diabetes and ER-negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes, but this was not seen in patients with ER-positive tumors (31).…”
Section: Introductionmentioning
confidence: 87%
“…Several studies have shown that pre-existing diabetes is associated with the presence of more advanced breast cancer at the time of the initial diagnosis [28,[32][33][34][35][36]. Some caution is necessary in attributing this observation to a diabetesinduced acceleration in tumor progression, because there are reports of lower participation rates of diabetic women in screening mammography for breast cancer compared with the general female population [37,38].…”
Section: Type 2 Diabetes and Breast Cancer Prognosismentioning
confidence: 97%